Health problems and risk factors prevailing among garment workers in Tirupur, Tamil Nadu - P. Ravichandran, Sreesupria; Shah, Pankaj B. (International Journal Of Community Medicine And Public Health, 2018)
Background: Garment workers are susceptible to various health problems by virtue of their workplace and working conditions. The present study was conducted to estimate the prevalence of certain health problems and to assess association between socio demographic factors, occupational factors and certain health problems among garment workers. Methods: A cross sectional study was conducted among garment industry workers, at Tirupur. Interview was conducted using a structured pretested questionnaire including information on visual problems, hypertension, diabetes, gastrointestinal symptom rating scale, American thoracic society, and division of lung disease –78 adult respiratory questionnaires. Clinical examination was done to assess body mass index and blood pressure was recorded. Visual acuity for distant and near vision was tested. Haemoglobin estimation was performed. Data entry and analysis was done using SPSS version 15 software. Chi-square test was used as a test of significance. Results: In this study, 87.4% of the workers reported any one health problem. The common problems reported were musculoskeletal problems (77.6%) followed by anaemia (57%), visual problems (51.6%), symptoms of respiratory problems (31.3%), hypertension (12.9%), diabetes (6.6%) and obesity (2.1%). 49.7% of the workers had any one symptoms of gastrointestinal problems in the last 7 days. The study has shown a possibility of older age, sewing work, sitting posture, and increased work experience as potential risk factors in the development of various health problems. Conclusions: Garment workers probably need long term on site awareness programs, continuous motivation and health education to prevent and treat these problems at an earlier stage.